Archaeology and agriculture: plants, people, and past land-use. (October 2021) - de Vareilles, Anne; Pelling, Ruth; Woodbridge, Jessie; Fyfe, Ralph
Abstract : As a specialised branch of archaeology requiring specific field and laboratory methodologies, the contributions of archaeobotany have often been overlooked by the ecological research community. Developments in the fields of botany, chemistry, and ancient DNA analyses have greatly increased the potential for archaeobotany to contribute to topical questions relating to the Anthropocene and landscape transformations. We review the role of archaeobotany in identifying and describing past arable land use. Analytical techniques are illustrated with examples at both local and regional scales, demonstrating how archaeobotany can provide unique details of the wide array of past subsistence and land-use strategies. These data and their potential should be better recognised as important information that could underpin models seeking to evaluate or predict the effects of socioenvironmental interactions. Highlights: Ancient plant remains hold information on past subsistence strategies and land use. Recent advances in the field of archaeobotany have broadened the range of techniques by which ancient plant remains can be studied. Archaeobotanical investigations show a diverse range of ancient farming practices and innovative solutions to social and natural pressures. Descriptions of ancient land use could be integrated into models of human–environment interactions, thus enabling a more accurate understanding of the impacts of past practices, and providing potential lessons for the future.